INTERNATIONAL EXPERIENCE IN THE RESTORATION OF RURAL AREAS AFTER ARMED CONFLICTS: LESSONS FOR UKRAINE - Качула, Світлана; Ластовченко, Павло (SWorldJournal, 2025)
The article examines the international experience of rural area recovery after armed conflicts and its potential application in Ukraine. The relevance of the topic is determined by the necessity to restore the socio-economic potential of rural areas affec